The Dilemma Facing Landlords and Tenants: Enforcing Tenancy Tribunal orders while Upholding Privacy Interests - Harbrow, Helena (Victoria University of Wellington Law Review, 2005)
Private landlords are the major contributors of housing in the New Zealand rental market. For years landlords have complained of an inability to enforce Tenancy Tribunal orders obtained against tenants for their failure to pay rent pursuant to the Residential Tenancies Act 1986. Following complaints, the Ombudsman controversially recommended that tenants’ address information held by government departments, in particular the Ministry of Social Development, be released to the Courts to facilitate the enforcement process. However, this solution fails to adequately address the source of the problem and further encumbers the success of the landlord tenant relationship. Without effective enforcement options landlords may revert to their own methods to safeguard their investments. This has lead to the formation of bad tenant registers on the internet and the plea for landlords to be able to access, among other things, tenants’ credit history as quasi credit providers under the Credit Information Privacy Code. During this process tenants’ privacy rights are being diminished, and their ability to access proper housing potentially compromised. Strategies that reduce the risk for landlords, by letting them know which tenants are likely to pay their rent from the outset, and by facilitating the retrieval of outstanding payments, will nurture the landlord tenant relationship.